Beyond disruption : innovate and achieve growth without displacing industries, companies, or jobs - Kim, W. Chan; Mauborgne, Renée (Ascent Audio, 2023)
Disruption dominates innovation theory and practice. But disruption is destructive-displacing jobs, companies, and even entire industries. Are we missing better, and even bigger, opportunities to innovate and grow? With three decades of research, W. Chan Kim and Renee Mauborgne reveal another way to innovate and grow. Just as their #1 global bestseller Blue Ocean Strategy redefined the essence of strategy as creating not competing, Beyond Disruption redefines and expands the existing view of innovation by introducing a new approach-nondisruptive creation-that is free from the destructive displacement that happens when innovators set out to disrupt. Kim and Mauborgne reveal the distinct advantages of nondisruptive creation to business and society, showing how this bold, new approach to innovation allows companies to grow while also being a force for good. With examples that cut across all sectors of the economy, this book shows: why nondisruptive creation matters to all of us and why it's about to become a lot more important in the future; how to create innovation strategies that trigger nondisruptive creation instead of disruption; how to identify and execute on nondisruptive opportunities; and how companies can more thoughtfully pursue their growth and innovation strategies in a way that better balances business and society.